2014
DOI: 10.7243/2050-2389-3-3
|View full text |Cite
|
Sign up to set email alerts
|

First products of DNA marker-assisted selection in sorghum released for cultivation by farmers in sub-saharan Africa

Abstract: Striga hermonthica (Del.) Benth. is the major biotic constraint to sorghum production. Its control is difficult and can only be achieved through integrated management strategies that depend mainly on host plant resistance and enhanced soil fertility. However, breeding for resistance is hampered by the complexity of host parasite interactions and lack of reliable screening methods. The invention of molecular markers has enhanced the effectiveness of breeding for resistance. Five genomic regions (QTLs) with link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Microsatellite markers linked to the low germination stimulant gene (lgs) for S. hermonthica were identified in sorghum and were supposed to be useful in breeding S. hermonthica-resistant sorghum varieties [14]. In breeding projects in Sudan and Eritrea, S. hermonthica resistance of sorghum was successfully improved by markerassisted selection [15,16]. Resistance to S. hermonthica in wild sorghum accessions was reported as novel sources for sorghum breeding, in which the resistance was ascribed to incompatibility [17].…”
Section: Sorghummentioning
confidence: 99%
“…Microsatellite markers linked to the low germination stimulant gene (lgs) for S. hermonthica were identified in sorghum and were supposed to be useful in breeding S. hermonthica-resistant sorghum varieties [14]. In breeding projects in Sudan and Eritrea, S. hermonthica resistance of sorghum was successfully improved by markerassisted selection [15,16]. Resistance to S. hermonthica in wild sorghum accessions was reported as novel sources for sorghum breeding, in which the resistance was ascribed to incompatibility [17].…”
Section: Sorghummentioning
confidence: 99%
“…Breeders practice MAS when an important trait that is difficult to assess phenotypically, is tightly linked to a Mendelian trait or molecular markers that can be easily scored (Lammerts van Bueren et al, 2010). The use of molecular markers to breed for Striga resistance in sorghum has recently been shown to be possible (Ejeta and Gressel, 2007;Gammar and Mohamed, 2013;Mohamed et al, 2014). Haussmann et al (2004) identified molecular markers linked to Striga resistance QTLs having mechanisms over and above the "low germination stimulant" trait.…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum (Sorghum bicolour (L.) Moench) is an important staple crop in Sub-Saharan Africa (SSA) that can meet the increasing demand of food [1]. Although, sorghum consumption is high in most SSA countries, the grain yield at the farm level is low due to the effect of biotic and abiotic stresses [2] [3].…”
Section: Introductionmentioning
confidence: 99%